Relationship between sexual partnerships, intimate partner violence and sexually transmitted infections in pregnant women living with HIV and not living with HIV in Cape Town, South Africa - Qayiya, Yamkela (Department of Public Health and Family Medicine, 2023)
Background: Women are at high risk of HIV and sexually transmitted infections (STIs) prior to and during pregnancy. There is limited research on the link between quality of sexual relationships, intimate partner violence (IPV) and STIs in pregnancy. This study aims to evaluate the association between relationship type and quality, IPV, and STI diagnosis in pregnant women. Methods We conducted a cohort study of 242 pregnant women ≥18 years attending their first antenatal care visit in Cape Town, South Africa between February 2017 and February 2019. We conducted interviews and tested pregnant women for three different STIs: Chlamydia trachomatis (CT), Neisseria gonorrhoea (NG) and Trichomonas vaginalis (TV) using point-of-care PCR testing (GeneXpert, Cepheid, USA). We used multivariable logistic regression to evaluate the association between relationship quality, STI, and IPV during pregnancy, adjusting for maternal age, gestational age and relationship status. Results In 242 pregnant women (median age 29 years [IQR = 24–34], and median gestational age 19 weeks [IQR= 14-24]), 78 (32%) were diagnosed with CT, NT, and/or TV at baseline. Unmarried, non-cohabiting women had almost 2-times the odds of having an STI during pregnancy (aOR=1.92, 95% CI=1.06-3.48); women living with HIV had increased odds of having an STI (aOR=1.97, 95% CI=1.07-3.62) adjusting for covariates. Overall, 5% of women who had an STI reported experiencing IPV during the past year (n=4) and 2% of the women who tested STI-negative (n=4). Women who reported having high relationship quality in their primary relationship had decreased odds of experiencing IPV (aOR=0.11, 95% CI=0.017-0.073) compared to those who reported low relationship quality, adjusting for covariates, but this was not associated with STI diagnosis. Reporting recent IPV was not associated with STI acquisition (aOR=2.41, 95% CI=0.55-10.45). Conclusion: We found a high prevalence of STIs among pregnant women. Women who were unmarried or noncohabiting with the father of the baby or were living with HIV had increased odds of having a STI during pregnancy. Women who reported better relationship quality were associated with decreased odds of experiencing IPV. Experiencing IPV was not associated with STI acquisition.